Pengaruh Layanan Bimbingan Kelompok dengan Teknik Self Control untuk Mengurangi Perilaku Konsumtif Online Shopping Siswa - Sholihat, Nadiyatus; Syafriadi, Non; Mardes, Siska (Universitas Batanghari Jambi, 2026)
This study aims to determine the influence of group guidance services with self-control techniques in reducing online shopping consumptive behavior in SMP Negeri 8 Pekanbaru students. This study uses a quantitative approach with the experimental method and the One Group Pretest-Posttest Design method. The research subjects totaled 10 students who were selected through purposive sampling techniques based on the results of high pretest consumptive behavior. The data collection instrument used a Likert scale questionnaire with four alternative answers, while data analysis was carried out through descriptive statistics, Wilcoxon test, and normalized N-Gain test. The results of the study showed a decrease in the level of online shopping consumptive behavior of students from the high and medium categories to the medium and low categories after being provided with group guidance services with self-control techniques. The results of the Wilcoxon test showed an Asymp value. The Sig (2-tailed) is 0.005 (< 0.05) which means there is a significant difference between before and after treatment. An average N-Gain value of 0.50 indicates the moderate effectiveness of the service provided. Thus, group guidance services with self-control techniques have been proven to be effective in reducing online shopping consumptive behavior in students.